Preparation of quaternary ammonium salt of chitosan nanoparticles and their textile properties on Antheraea pernyi silk modification. Issue 19 (November 2014) - Lu, Yanhua; Cheng, Dehong; Lu, Sheng; Huang, Fengyuan; Li, Gang
A novel eco-friendly finishing agent of quaternary chitosan nanoparticles was prepared in two steps from a chitosan with low molecular weight. The water-soluble quaternary ammonium salt of chitosan, N -[(2-hydroxy-3-trimethylammonium)propyl] chitosan chloride (HTCC), was first synthesized in heterogeneous system by quaternization, and then HTCC was further prepared to nanoparticles via ionotropic gelation reaction in the presence of 1, 2, 3, 4-butane tetracarboxylic acid and sodium hypophosphite. The size distribution and morphology of the HTCC particles were characterized using a laser particle size analyzer and transmission electron microscope (TEM). When Antheraea pernyi ( A. pernyi ) silk fabric was treated with HTCC nanoparticles by using a conventional dip-pad-dry-cure process, the modified A. pernyi silk fabric demonstrated durable wrinkle-resistant property, shrinkage-resistant property and antimicrobial activities against Staphylococcus aureus and Escherichia coli, even after being exposed to 50 consecutive home-laundering conditions. However, the modification of A. pernyi silk fabric caused breaking strength loss, breaking elongation reduction and initial modulus rise to some extent.